1982
DOI: 10.1016/s0072-968x(82)80006-5
|View full text |Cite
|
Sign up to set email alerts
|

Compression-Arthrodesis of Finger Joints using Kirschner Wires and Cerclage

Abstract: A retrospective series of forty-three finger joint arthrodesis is presented. The failure rate was seven per cent. A new method of introducing a cerclage wire into bone is demonstrated. Septic arthritis of finger joints is considered to be an indication for acute arthrodesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
10

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 7 publications
1
14
0
10
Order By: Relevance
“…6 Another study reported a 38% rate of nonunion for posttraumatic arthritis. 10 Compression has been a key point in the evolution of hardware for arthrodesis, improvement of union rates, time to union, and time to return to work. 2,11 Several studies have reported the results of compression screw techniques, ranging from 0% to 15% nonunion and from 14% to 44% overall complications (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Another study reported a 38% rate of nonunion for posttraumatic arthritis. 10 Compression has been a key point in the evolution of hardware for arthrodesis, improvement of union rates, time to union, and time to return to work. 2,11 Several studies have reported the results of compression screw techniques, ranging from 0% to 15% nonunion and from 14% to 44% overall complications (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…10 Nonunion and malunion are generally identified with the presence of a radiolucent line on radiographs. We believe that after a minimum 6-month follow-up, satisfactory retrospective evaluation can be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Die Ergebnisse von Arthrodesen mit intraossärer Drahtnaht haben u. a. Buck-Gramcko und Oehme, Brüser und Noever sowie Høgh und Jensen beschrieben (▶Tab. 2) [10,12,79].…”
Section: Die Intraossäre Drahtnahtunclassified
“…Hierfür können Fingerschienen eingesetzt werden, einige Autoren setzen hierfür aber auch einen Unterarmgips bzw. -cast oder eine Intrinsic-Plus-Schiene unter Einschluss des benachbarten Fingers ein und Wechseln im Verlauf, häufig nach 14 Tagen, auf eine Fingerschiene [8,26,32,64,74,79,80,85].…”
Section: Nachbehandlungunclassified
“…1,2 These include the cup-and-cone, 2 the convex-concave, 3 the dowell fusion, 4,5 end-on-mitring, 6 the AO, 7,8 the tension-band, 9 intraosseous wiring 10 and the intramedullary peg techniques. 11,12 The reported rate of failure ranges from 2% to 15% and complications include infection, malunion and pseudarthro-O sis.…”
mentioning
confidence: 99%